Synthesis, Characterization, and Anti-oxidant Evaluation of Novel Coumarin–Pyrazoline Derivatives: Sintesis, Karakterisasi, dan Evaluasi Antioksidan Derivatif Kumarin–Pirazolin Baru - Mohan, Ahmed Kadhim; Raheem, Leaqaa Abdulredha; Suwaid, Maan Abdul-Razzaq (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Oxidative stress is a major contributor to the pathogenesis of chronic diseases such as cancer and cardiovascular disorders. Specific Background: Coumarin and pyrazoline derivatives are known for their pharmacological activities, particularly their antioxidant potential. Knowledge Gap: However, limited studies have explored the synthesis and evaluation of coumarin–pyrazoline hybrids as potent free radical scavengers. Aims: This study aimed to synthesize and characterize novel coumarin–pyrazoline derivatives and evaluate their antioxidant activity using the DPPH assay. Results: Six new compounds were synthesized and structurally confirmed by ¹H-NMR, ¹³C-NMR, and mass spectrometry. Compounds 2 and 5 exhibited superior antioxidant activity compared to ascorbic acid, with IC₅₀ values of 18.3 μM and 19.7 μM, respectively, versus 23.9 μM for ascorbic acid. Novelty: The enhanced activity was attributed to specific functional groups: the methoxy group in compound 2 and the dimethylamino group in compound 5. Implications: These findings support the potential of coumarin–pyrazoline hybrids as promising antioxidant agents and lay the groundwork for future therapeutic development targeting oxidative stress-related conditions.Highlight : Coumarin–pyrazoline compounds 2 and 5 showed stronger antioxidant activity than ascorbic acid. Structures were confirmed through ¹H NMR, ¹³C NMR, and mass spectrometry. Antioxidant efficiency is linked to specific functional groups like OCH₃ and N(CH₃)₂ Keywords : Anti-oxidant activity, Coumarin, DPPH assay, Pyrazoline, IC50